Earthquake Moment Tensor Analysis Using Broadband Seismic Waveforms - Ahmed, Omar Qadir (Sulaimani Journal for Pure and Applied Sciences, 2018)
In this study the focal mechanisms are determined for the broadband waveforms of the earthquakes occurred in Kurdistan region, NE-Iraq and west of Zagros Mountains which are recorded by Sulaimani and Duhok University Observatories and Observatory and Earthquake Research Institute using moment tensor analysis. The seismic moment, depth and the nature of responsible fault that ruptured at the source are calculated by the waveform inversion. The inversion technique used is a grid search over the strike, dip and rake angles for each depth from 0.5 to 39 km in increments of 1 km. The observed and predicted waveforms are filtered and compared using bandpass filters and a proper velocity model for the Green’s function. The mechanism to the best fit was determined and the regional stresses was characterized in the study area. The results indicate a combination of mostly strike-slip with some dip-slip and oblique-slip motion.
Keywords: Focal mechanism; Moment tensor inversion; Earthquakes; Seismic waves